Effect of cardiac resynchronization therapy on pulmonary function in patients with heart failure - Cundrle, Ivan; Johnson, Bruce D; Somers, Virend K; Scott, Christopher G; Rea, Robert F; Olson, Lyle J (The American journal of cardiology, 2013)
Pulmonary congestion due to heart failure causes abnormal lung function. Cardiac resynchronization therapy (CRT) is a proven effective treatment for heart failure. The aim of this study was to test the hypothesis that CRT promotes increased lung volumes, bronchial conductance, and gas diffusion. Forty-four consecutive patients with heart failure were prospectively investigated before and after CRT. Spirometry, gas diffusion (diffusing capacity for carbon monoxide), cardiopulmonary exercise testing, New York Heart Association class, brain natriuretic peptide, the left ventricular ejection fraction, left atrial volume, and right ventricular systolic pressure were assessed before and 4 to 6 months after CRT. Pre- and post-CRT measures were compared using either paired Student's t tests or Wilcoxon's matched-pair test; p values <0.05 were considered significant. Improved New York Heart Association class, left ventricular ejection fraction, left atrial volume, right ventricular systolic pressure, and brain natriuretic peptide were observed after CRT (p <0.05 for all). Spirometry after CRT demonstrated increased percentage predicted total lung capacity (90 ± 17% vs 96 ± 15%, p <0.01) and percentage predicted forced vital capacity (80 ± 19% vs 90 ± 19%, p <0.01). Increased percentage predicted total lung capacity was significantly correlated with increased peak exercise end-tidal carbon dioxide (r = 0.43, p = 0.05). Increased percentage predicted forced vital capacity was significantly correlated with decreased right ventricular systolic pressure (r = -0.30, p = 0.05), body mass index (r = -0.35, p = 0.02) and creatinine (r = -0.49, p = 0.02), consistent with an association of improved bronchial conductance and decreased congestion. Diffusing capacity for carbon monoxide did not significantly change. In conclusion, increased lung volumes and bronchial conductance due to decreased pulmonary congestion and increased intrathoracic space contribute to an improved breathing pattern and decreased hyperventilation after CRT. Persistent alveolar-capillary membrane remodeling may account for unchanged diffusing capacity for carbon monoxide.
Keywords: respirační funkční testy; respirační insuficience; Cardiac Resynchronization Therapy; Male; srdeční selhání; plíce; následné studie; prognóza; Aged; mužské pohlaví; senioři; Severity of Illness Index; Follow-Up Studies; Lung; lidé; ženské pohlaví; Humans; Heart Failure; Respiratory Function Tests; fyziologie dýchací soustavy; Prognosis; Respiratory Physiological Phenomena; srdeční resynchronizační terapie; Respiratory Insufficiency; stupeň závažnosti nemoci; Female